EVALUASI KINERJA ON FARM AGRIBUSINESS DALAM MENDUKUNG TERWUJUDNYA P4S BELIMBING ARTHA MANDIRI SEBAGAI AGROWISATA - Anggarani, Susanti Dewi; Asnah, Asnah; Dyanasari, Dyanasari (BUANA SAINS, 2023)
This study aimed to know about the interrelationships between agribusiness subsystems, cost analysis, revenues, and profits in the development of starfruit in P4S Belimbing Artha Mandiri and to analyze the feasibility and sustainability of developing starfruit in P4S Belimbing Artha Mandiri. The analysis used is descriptive, cost analysis, sweet star fruit income, and financial feasibility analysis. The results showed that the agribusiness subsystems in P4S Belimbing Artha Mandiri were interrelated and supported one another and still have weaknesses in the processing and marketing subsystems. Over ten years, it has had an average revenue of Rp. 786,266,944, - with an average operational cost of Rp. 360,793,236, - so the average income received each year is Rp. 425,473,707, - There are four criteria for financial eligibility. The Net Present value (NPV) shows a value of Rp. 1,453,862,787.- IRR (Internal Rate of Return) shows a value of 41.72%, and PP (Payback Period) is at 1.26. The calculation of Net B/C in business starfruit cultivation is 3.87. The financial feasibility criteria show that the sweet star fruit cultivation business at P4S Belimbing Artha Mandiri is feasible and can continue.